Optically Pumped Lasing from Hybrid Perovskite Light‐Emitting Diodes. Issue 1 (6th November 2019) - Kim, Hoyeon; Roh, Kwangdong; Murphy, John P.; Zhao, Lianfeng; Gunnarsson, William B.; Longhi, Elena; Barlow, Stephen; Marder, Seth R.; Rand, Barry P.; Giebink, Noel C.
Abstract: Electrically pumped lasing from hybrid organic–inorganic metal‐halide perovskite semiconductors could lead to nonepitaxial diode lasers that are tunable throughout the visible and near‐infrared spectrum; however, a viable laser diode architecture has not been demonstrated to date. Here, an important step toward this goal is achieved by demonstrating two distinct distributed feedback light‐emitting diode architectures that achieve low threshold, optically pumped lasing. Bottom‐ and top‐emitting perovskite light‐emitting diodes are fabricated on glass and Si substrates, respectively, using a polydimethylsiloxane stamp in the latter case to nanoimprint a second‐order distributed feedback grating directly into the methylammonium lead iodide active layer. The devices exhibit room temperature thresholds as low as ≈6 µJ cm −2, a peak external quantum efficiency of ≈0.1%, and a maximum current density of ≈2 A cm −2 that is presently limited by degradation associated with excessive leakage current. In this low current regime, electrical injection does not adversely affect the optical pump threshold, leading to a projected threshold current density of ≈2 kA cm −2 . Operation at low temperature can significantly decrease this threshold, but must overcome extrinsic carrier freeze‐out in the doped organic transport layers to maintain a reasonable drive voltage. Abstract : Optically pumped lasing is demonstrated in distributed feedback hybrid perovskite light emitting diodes fabricated on both glass and Si substrates. Thresholds as low as ≈6 µJ cm −2 at room temperature are achieved and retained under ≈2 A cm −2 of pulsed electrical excitation.